O desenvolvimento de livros sensoriais como materiais de apoio para o ensino de habilidades matemáticas na educação infantil: uma perspectiva inclusiva considerando discentes com deficiência visual - Francisco, Heleine Cristina Villas Bôas (Universidade Federal de São Carlos, 2021)
This work presents a study in the area of Mathematics Teaching, focusing on the teaching of mathematical skills to students of Early Childhood Education with visual impairment, in the perspective of Inclusive Education, due to the presence, increasingly expressive, of these students in nursery schools. . The aim of this study is to produce educational materials for teaching mathematical skills to children aged 0 to 5 years. To this end, the research had as its starting point a bibliographic survey to identify scientific works and publications produced in the area, presented in the last six years (2015-2020) in the Google Scholar databases and in the scientific event ENEMI-2019, aimed at the teaching of inclusive mathematics. Content Analysis, Bardin (2003), was used as a data analysis technique, using na exploratory and qualitative approach. The results of the research demonstrated that of the total of 69 works found focus edon teaching mathematics to students with visual impairments, 27 of them dealt with the use of didactic materials and methodological resources for teaching inclusive mathematics, and of these,only 3 publications dealt with, specifically from the sensorial book, demonstrating the scarcity of the elaboration and use of this material in the teaching of blind children. Base dont he theoretical frameworks found in the research: Ochoa (2015), Jacob (2017) and Moraes, Santos and Sales (2020), the assumptions found regarding the potential and limitations of the sensory book as a support tool for the teaching of students with disabilities visual, andt he BNCC (2017) precepts for the regulation of Early Childhood Education, the methodology for preparing the educational product was developed from the contributions of Káplun (2003), Ruiz (2007) and Leite (2019) and the making of oft he two volumes of sensory books for teaching mathematical skills to blind children in Early Childhood Education, in an inclusive perspective, with the second volume remaining for completion in future research, due to the difficulties encountered by the COVID-19 pandemic. The sensory books were planned and developed with the objective of complementing the didactic material of the teacher to assist classes with children with disabilities, however, the multi proposal sensorial explored in the material serves as a resource stimulated involve students in the classroom, since it explores all sense organs, facilitating learning. In this sense, the sensory book was developed and became an excellent inclusive tool in the classroom. Thus, this research aims contribute to the teaching and learning of blind and low vision children in the area of Mathematics, in addition encouraging inclusive pedagogical practices in the school context.
The development of sensory books as support materials for teaching math skills in early childhood education: an inclusive perspective considering students with visual impairments
Keywords: Educação Inclusiva; Cegueira; Didática multissensorial; Matemática; Educação Infantil; Inclusive education; Blindness; Multisensory didactics; Math; Child education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM